Utang Luar Negeri: Menelisik Faktor Penyebab, Kondisi di Indonesia, dan Dampaknya Terhadap Perekonomian - Nova Adella; Rani Wulandari; Alfa Rizki Saputra; Heni Noviarita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Foreign debt (ULN) is one of the important issues in the dynamics of the global economy, especially for developing countries. This study aims to analyze the causal factors, conditions of ULN in Indonesia, and its impact on the economy. Qualitative research methods with a literature approach were used to collect data from various written sources. The results of the study indicate that the factors causing ULN in Indonesia include the inability to provide sufficient development funds, an imbalance between investment and savings, and dependence on imported goods. The impact of ULN on the Indonesian economy is divided into positive and negative impacts. The positive impacts include effective sources of development financing, recognition of the country's ability to pay off debt, the establishment of relations between countries, and encouragement of domestic policy improvements. The negative impacts include the burden on the APBN, reduction in spending strategies, the influence of creditor countries in policy making, and the stigma of being a failed state. The study concludes that ULN in Indonesia needs to be managed wisely by considering long-term risks. Some recommended solutions include delaying principal debt payments, changing payment obligations, and reducing principal debt. This study provides important information for policy stakeholders and the Indonesian public in understanding the importance of wise ULN management to encourage sustainable economic growth and improve people's welfare.